Emergency Department presentations with suicidal ideation: A missed opportunity for intervention? - Ross, Emma; Maguire, Aideen; O'Hagan, Denise; O'Reilly, Dermot (International Journal of Population Data Science, 2023)
Objectives Suicidal ideation constitutes a central element of most theories of suicide. Despite its prevalence, most research has focused on other suicidal behaviours such as self-harm. This study examines the characteristics of those presenting to EDs with suicidal ideation and quantifies the associated risk of suicide and other causes of death. Methods This retrospective cohort study used population-wide health administration data linked to data from the Northern Ireland Registry of Self-Harm and centrally held mortality records from April 2012 to December 2019. Mortality data, coded as suicide, all-external causes and all-cause mortality was analysed using Cox proportional hazards. Additional cause-specific analyses included accidental deaths, deaths from natural causes, and drug and alcohol-related causes. Results The final cohort comprised 1,662,118 individuals aged over 10 years, of whom 15,267 presented to the ED with ideation during the study period. Individuals with ideation had a ten-fold increased risk of death from suicide (HRadj=10.84, 95% CI 9.18, 12.80) and from all external causes (HRadj=10.65, 95% CI 9.66, 11.74) and a three-fold risk of death from all causes (HRadj= 3.01, 95% CI 2.84, 3.20). Further cause-specific analyses indicated that risk of accidental death (HRadj=8.24, 95% CI 6.29, 10.81), alcohol-related death (HRadj=10.57, 95% CI 9.07, 12.31), and drug-related death (HRadj=15.17, 95% CI 11.36, 20.26) were also significantly raised. There were few socio-demographic and economic characteristics that would identify which of these patients are most at risk of suicide or other causes of death. Conclusions The identification of those experiencing ideation is recognised to be important yet difficult in practice. The ED represents an important potential intervention point for this hard-to-reach population. However, and unlike those presenting with self-harm, clinical guidelines for the management and recommended best practice and care of these individuals are lacking.